Theories of the state : the politics of liberal democracy - Dunleavy, Patrick (Meredith Press, 1987)
Discusses Pluralist, New Right, Elitist, Marxist and Neo-pluralist theories. Provides summary of intellectual origins, methodology and key strengths and weaknesses with examples from United States, Western Europe, etc.